2017
DOI: 10.5812/amh.61661
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison between Digital Subtraction Angiography, CT Angiography, and Doppler Ultrasonography in Evaluation and Assessment of Carotid Artery Stenosis

Abstract: Background: Common angiography or digital subtraction angiography (DSA) is the gold standard protocol for diagnosis of carotid artery stenosis. However, this method has very high delivered X-ray doses to patient and personnel as an invasive diagnostic protocol. The progress of noninvasive or minimally invasive diagnostic techniques like Doppler ultrasonography (DUS), CT angiography (CTA), and MR angiography (MRA) has improved the detection and evaluation of stenosis lesions. The aim of this study was to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
2
1
0
Order By: Relevance
“…Polarised light microscopy identi ied two different types of plaques, a soft one with a transparent structure and without the presence of bone tissue, called soft plaques, and hard plaques with woven bone structures. These indings are probably identical with echolucent (predominant lipid core) und echo-opaque plaques (predominantly ibrous tissue/ calcium) as identi ied by sonography and magnetic resonance tomography [27][28][29][30][31]. The major inding of our study is the presence of woven bone tissue in hard carotid plaques.…”
Section: Discussionsupporting
confidence: 82%
“…Polarised light microscopy identi ied two different types of plaques, a soft one with a transparent structure and without the presence of bone tissue, called soft plaques, and hard plaques with woven bone structures. These indings are probably identical with echolucent (predominant lipid core) und echo-opaque plaques (predominantly ibrous tissue/ calcium) as identi ied by sonography and magnetic resonance tomography [27][28][29][30][31]. The major inding of our study is the presence of woven bone tissue in hard carotid plaques.…”
Section: Discussionsupporting
confidence: 82%
“…Based on these results, it can be concluded that the PSV ICA/ICA ratio should be included among the commonly used parameters for the evaluation of carotid stenosis. These results are in concordance with a recently published study (28).…”
Section: Discussionsupporting
confidence: 94%
“…Digital subtraction angiography (DSA) was the diagnostic modality of choice in the past; however, unless the results of non-invasive investigations are inconclusive and angiography is part of a therapeutic intervention, clinical guidelines advise against performing diagnostic angiography with selective carotid artery catheterisation due to the increased risk of stroke and distal embolisation from wire and catheter manipulation in the arch and its branches in addition to access site complications [ 16 ].…”
Section: Patient Preparationmentioning
confidence: 99%